Differentiated TB care matrix: Validating an assessment tool for healthcare workers providing differentiated TB care using Delphi technique - Riswana S. Ansari; Ankeeta Menona Jacob; Avinash K. Shetty; Shazia Anjum (Clinical Epidemiology and Global Health)
Introduction: The provision of Differentiated Tuberculosis (TB) Care by healthcare personnel is crucial in optimising patient outcomes and resource utilisation in TB units. This study explores validating a questionnaire on differentiated TB care provision from the healthcare providers' perspective, focusing on facilitating factors and challenges in the healthcare delivery for TB patients using the Delphi Technique. Methods and materials: A multidimensional model was designed to assess differentiated TB care provision by healthcare providers in Karnataka using inductive and deductive methods. Between January 2024 and March 2024, we used the Delphi technique via email and in-person contacts. We engaged a panel of Ten Subject Matter Experts (SMEs) to refine and validate the assessment tool containing 146 items iteratively using 2 rounds of 5 SMEs each. For each round, the following metrics were calculated: Lawshe's Content Validity Ratio (CVR), Scale Content Validity Indices (CVI), and Item Impact Score (IIS, Face Validity). The final tool contained only questions with Item Impact Scores of ≥1.5, CVRs of ≥0.99, and CVIs of ≥0.8 (p-value <0.05). Results: The Item Impact Score (Face Validity) of 126 items accepted as facilitating factors and barriers in providing Differentiated TB care by Community Health Officers and Medical officers for TB patients was ≥1.5. Content Validity Ratios (CVR) for the facilitating factors and barriers in providing differentiated TB care by Community Health Officers and Medical Officers for TB patients was ≥0.99, except for 19 items removed from the final tool. The Scale Content Validity Indices (for relevance), i.e., S-CVI (Average) and S-CVI (Proportional relevance), for 19 items that were removed from the tool failed to reach ≥0.8. Conclusions: By determining acceptable content validity ratios and indices using the Delphi technique, this study has developed and validated a tool to assess the facilitating factors and barriers in providing differentiated TB care by the Community Health Officers and Medical Officers for TB patients.